Spleen and Liver Volumetrics as Surrogate Markers of Hepatic Venous Pressure Gradient in Patients With Noncirrhotic Portal Hypertension. Issue 8 (16th July 2018) - Etzion, Ohad; Takyar, Varun; Novack, Victor; Gharib, Ahmed M.; Canales, Raissa; Adebogun, Akeem; Matsumoto, Eric; Eccleston, Jason L.; Kleiner, David E.; Rosenzweig, Sergio D.; Gunay‐Aygun, Meral; Uzel, Gulbu; et al.
Abstract : Noncirrhotic portal hypertension is an uncommon and often overlooked cause of portal hypertension. Non‐invasive markers of NCPH are lacking. Spleen and liver volumetrics are shown to correlate with HVPG measurements and may have utility in the assessment of NCPH as a noninvasive biomarker. Abstract : Noncirrhotic portal hypertension (NCPH) is a rare disease that may lead to serious clinical consequences. Currently, noninvasive tools for the assessment of NCPH are absent. We investigated the utility of spleen and liver volumetrics as a marker of the presence and severity of portal hypertension in this population. A cohort of NCPH patients evaluated between 2003 and 2015 was retrospectively studied. The association of spleen and liver volumes with the hepatic venous pressure gradient (HVPG) level was evaluated using locally weighted scatterplot smoothing curves. A cohort of patients with viral hepatitis‐related liver disease was used as controls. Of the 86 patients with NCPH evaluated during the study period, 75 (mean age, 35 ± 17; 73% males) were included in the final analysis. Patients with portal hypertension had significantly higher spleen and liver to body mass index (BMI) ratios compared to patients with HVPG <5 mm Hg (39.5 ± 27.9 versus 22.8 ± 10.6 cm 3 /kg/m 2, P = 0.003; 91.1 ± 40.1 versus 71.4 ± 16.7 cm 3 /kg/m 2, P = 0.014, for spleen/BMI and liver/BMI, respectively). In contrast to the patients with viral hepatitis, a positive linear correlation was observed in the NCPH cohort between spleen/BMI and liver/BMI (above a cutoff of 25 and 80 cm 3 /kg/m 2, respectively) and HVPG level. Additionally, only in the NCPH cohort was an increase in spleen/BMI range quartile predictive of a higher prevalence of portal hypertension and clinically significant portal hypertension (trend, P = 0.014 and 0.031, respectively). Conclusion: Spleen and liver volumetrics may have utility in the assessment of NCPH as a noninvasive biomarker that can be performed using routine radiologic examinations. Further studies are needed to validate these findings. ( Hepatology Communications 2018; 00:000‐000)